INSTITUTIONALIZATION OF LOCAL WISDOM WEDDING PROCESSES IN CULTURE OF PUSAR VILLAGE, BATURAJA SUB-DISTRICT OGAN KOMERING ULU DISTRICT - Icuk Muhammad Sakir; Marleni Marleni; Indah Pusnita (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2023)
Culture is a knowledge system that includes a system of ideas contained in the human mind, so that in everyday life culture is abstract. The wedding procession with sacrifice, the slaughter of a scapegoat for the people of Pusar Village is one of the traditions owned by the people of Pusar Village, Baturaja District. The approach used in the meaning of verbal and nonverbal communication in a series of marriage processions with sacrifices, the slaughter of scapegoats uses symbolic interaction theory, symbolic interaction theory holds that individuals form the same meaning through communication. The method used is descriptive qualitative method. In collecting data, conducting in-depth interviews (Depth Interview) to key informants, the selected informants are people who are considered to know and understand the problems studied. The results of the analysis in this study are marriage processions with sacrifices, slaughtering scapegoats in Pusar Village there are forms of verbal communication and nonverbal communication contained in every series of marriage processions with sacrifices, slaughtering scapegoats including prayer. The prayer delivered by the traditional leader and followed by the family holding a wedding ceremony aims to request permission to hold a wedding ceremony and share happiness with the ancestors. After taking turns praying, the family waters the graves of their ancestors with the water that has been provided. From the results of the research conducted, it can be concluded that in every series of wedding processions with sacrifices, the slaughter of a scapegoat has a meaning that has been believed by the people of Pusar Village itself. It is hoped that the people of OKU Regency can participate in preserving the existing culture and arts. Especially in the cultural arts of the wedding procession with sacrifice, the slaughter of this scapegoat.